Evaluasi kuantitatif penggunaan antipsikotik pada pasien skizofrenia dengan metode ATC/DDD dan DU 90% di RSJ Tampan Provinsi Riau tahun 2023 - Novia Sinata; Defrika Dian Tami; Erniza Pratiwi (Jurnal SAGO Gizi dan Kesehatan, 2026)
Background: Schizophrenia is a major cause of disability, and antipsychotics are the main pharmacological treatment. Their use requires evaluation because adverse effects may affect treatment safety and adherence. Antipsychotic utilization among inpatients at RSJ Tampan has not previously been evaluated using the World Health Organization (WHO) ATC/DDD and DU 90% methods.Objectives: This study aimed to quantitatively evaluate antipsychotic utilization among inpatients with schizophrenia using the ATC/DDD and DU 90% methods.Methods: This descriptive observational study used a retrospective review of medical records from January to December 2023. A total of 101 records that met the eligibility criteria were selected through purposive sampling. Antipsychotic utilization was calculated as defined daily doses (DDD) per 100 bed-days. Drugs were ranked by utilization volume, and cumulative percentages were used to identify the DU 90% segment.Results: Total antipsychotic utilization was 123.82 DDD/100 bed-days and was dominated by typical antipsychotics. Five drugs comprised the DU 90% segment: haloperidol (74.58 DDD/100 bed-days; 60.23%), risperidone (14.95; 12.07%), aripiprazole (14.42; 11.65%), fluphenazine (5.36; 4.33%), and trifluoperazine (4.73; 3.82%), with a cumulative proportion of 92.10%.Conclusion: Antipsychotic utilization was concentrated in five drugs, with haloperidol accounting for the largest proportion. These quantitative findings support further evaluation of prescribing appropriateness and treatment safety.